Approaching Solar‐Grade a‐Si:H for Photovoltaic Applications via Atmospheric Pressure CVD Using a Trisilane‐Derived Liquid Precursor. Issue 7 (23rd June 2017) - Cádiz Bedini, Andrew P.; Trieu, Long D.; Muthmann, Stefan; Rau, Uwe; Carius, Reinhard
Abstract : The article demonstrates the fabrication of a‐Si:H thin films in a N2 ‐filled glove box via atmospheric pressure chemical vapor deposition (APCVD) using a vaporized silicon hydride polymer/silicon nanoparticle composite ink prepared from trisilane (Si3 H8 ). It is shown via Raman spectroscopy that the films exhibit good short and mid‐range atomic order. Fourier transform infrared spectroscopy reveals a fairly compact microstructure and a hydrogen concentration of 13–18 at.%. Photothermal deflection spectroscopy demonstrates a sub band gap absorption only a factor of ∼6 higher than that of solar‐grade plasma‐enhanced CVD (PECVD) material. As a demonstration of the utility of our ink, c‐Si wafer surface passivation layers are deposited resulting in effective minority charge carrier lifetimes exceeding 400 μs. These lifetimes constitute the as of yet the highest reported values achieved using liquid precursors for bifacial coating without subsequent hydrogen radical treatment. The high electronic quality of the layers is shown via the fabrication of a n‐i‐p thin‐film solar cell with an APCVD intrinsic absorber layer exhibiting an efficiency of 3.4% and hence, placing its photovoltaic performance among the highest reported for cells processed from the liquid phase and without a back reflector. Abstract : The fabrication of a‐Si:H thin films via atmospheric pressure CVD is demonstrated using a precursor ink prepared from semiconductor‐grade purity trisilane (Si3 H8 ). Various spectroscopic techniques are used to characterize the absorption and structural properties of the films. The material is implemented as the surface passivation layers and as the light absorber in an n‐i‐p thin‐film solar cell.